Economics of antiretroviral treatment vs. circumcision for HIV prevention - Bärnighausen, Till; Bloom, David E.; Humair, Salal (Proceedings of the National Academy of Sciences of the United States of America, 2012)
The HIV Prevention Trials Network (HPTN) 052 study, which showed the effectiveness of antiretroviral treatment in reducing HIV transmission, has been hailed as a “game changer” in the fight against HIV, prompting calls for scaling up treatment as prevention (TasP). However, it is unclear how TasP can be financed, given flat-lining support for global HIV programs. We assess whether TasP is indeed a game changer or if comparable benefits are obtainable at similar or lower cost by increasing coverage of medical male circumcision (MMC) and antiretroviral treatment (ART) at CD4 <350/μL. We develop a new mathematical model and apply it to South Africa, finding that high ART coverage combined with high MMC coverage provides approximately the same HIV incidence reduction as TasP, for